INFLUENCE OF PRICE DISCOUNT AND SALES PROMOTION ON IMPULSE BUYING AZWA PERFUME PEKANBARU - Vikario Solenski; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the influence between Price Discount and Sales Promotion Against Impulse Buying Azwa Perfume Pekanbaru. Price discount is a discount on the agreed sale price if payment is made within a period of time faster than the credit term or cash deductions when viewed from the point of sale (Ismaya, in Kasimin et al 2014: 3). The next variable is Sales promotion, is a company promotion program in order to encourage sales or to increase sales or in order to maintain the interest of customers to keep shopping at it (Ma'ruf, in Kasimin et al 2014: 3). The two variables in this study are thought to have an effect on Impulse Buying. Impulse Buying itself is nothing new in the marketing world, but it is very interesting to research. This research was conducted at Azwa Perfume Pekanbaru. This study took the number of respondents as many as 94 people.Data obtained through questionnaires. The data from the questionnaire is further processed using statistical analysis that is simple linear analysis, multiple linear analysis, determination analysis, and significance test with t test (partial), F (simultaneous) test.The results show that the hypothesis of this study is acceptable. Where meaning price discount and sales promotion simultaneously significantly influence impulse buying Azwa Perfume Pekanbaru.Keywords: Price Discount, Sales Promotion, Impulse Buying